Clinicopathological Features of Early and Late Recurrence of Endometrial Carcinoma After Surgical Resection. Issue 5 (June 2017) - Takahashi, Akimasa; Matsuura, Motoki; Matoda, Maki; Nomura, Hidetaka; Okamoto, Sanshiro; Kanao, Hiroyuki; Kondo, Eiji; Omatsu, Kohei; Kato, Kazuyoshi; Utsugi, Kuniko; Takeshima, Nobuhiro
Abstract : Objectives: The incidence of endometrial carcinoma has been increasing annually in developed nations; it is currently the second most common gynecological malignancy. Although the majority of patients are diagnosed at an early stage, 15% to 20% reportedly recur; consequently, patients are usually followed clinically for 3 years after the initial curative surgery. We therefore aimed to determine the incidence and clinicopathological features of early and late recurrences of endometrial carcinoma after surgical resection. Materials and Methods: This retrospective study was performed using the clinical records of 2233 patients who underwent surgical resection for endometrial carcinoma between January 1970 and December 2009 at a single cancer center. Tumor recurrences were classified as early (<5 years) and late (>5 years) after initial surgery. Clinicopathological variables and tumor recurrence patterns were compared between the early and late recurrence groups. Survival analysis was performed using the Kaplan-Meier method. Results: Among 2233 study patients, 255 (11.4%) experienced endometrial carcinoma recurrence; of these, early and late recurrences occurred in 232 (91.0%) and 23 (9.0%) patients, respectively. Late recurrence was associated with invasion of less than half of the myometrium at diagnosis and the presence of histopathological features of endometrioid adenocarcinoma with low- or intermediate-grade histological subtype and absence of lymphovascular invasion. After recurrence, there was no significant difference in overall survival between the early and late recurrence groups ( P = 0.437). Furthermore, surgical treatment was associated with a significantly improved prognosis in the late recurrence group ( P = 0.044). Conclusions: The findings of this study indicated that patients who initially underwent successful treatment for low-grade and early-stage endometrial carcinoma should be followed clinically for more than 5 years. In cases of late recurrence, surgical management may improve prognosis.